Pengaruh Current Ratio Terhadap Return on Equity Pada PT Kino Indonesia Tbk Periode 2015–2025 - M. Reza Brahmana; Mulia Inda Purwati; Mukti Hadianto (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2026)
This study aims to determine and analyze the effect of the Current Ratio (CR) on Return on Equity (ROE) at PT Kino Indonesia Tbk for the period 2015–2025. This research employs a quantitative approach with an associative research design. The data used are secondary data obtained from the company's annual financial statements. The data analysis techniques include classical assumption tests, simple linear regression analysis, partial t-test, and coefficient of determination (R²). The results show that the Current Ratio has a negative and significant effect on Return on Equity. This is indicated by a regression coefficient value of -0.489 and a significance value of 0.001 (< 0.05). In addition, the coefficient of determination (R Square) is 0.734, which means that 73.4% of the variation in Return on Equity can be explained by the Current Ratio, while the remaining 26.6% is influenced by other factors outside this study. These findings indicate that excessively high liquidity tends to reduce the company’s profitability, suggesting inefficient management of current assets. Therefore, companies need to maintain a balance between liquidity and profitability to improve overall financial performance